PEREDAM PANAS PADA ATAP ALUMUNIUM DENGAN MENGGUNAKAN SPONS AIR - Husna Noor Mufida; Muh Syukri Ahsani; Masturi Masturi; Ian Yulianti (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The use of aluminum roof is already widely used, but leads to the room temperature becomes hot due to the high thermal conductivity. So far the impact of the heat generated is reduced with the installation of plasterboard and make a high roof. In this study, the reduction of heat on the aluminum roof with the installation of a sponge of water flowed. The research objective to reduce the temperature in the room because the water has a high specific heat. Research carried out by making a miniature model of aluminum-roofed house placed in the middle of the field during the sunny day. The bottom side of the aluminum fitted with a sponge and then underneath waterproof plastic coated (banner MMT). Water flowed slowly to keep the temperature inside the miniature house. The variable that changed was the thickness of the sponge layer. The air temperature measured with a thermometer in the room space and the outside air temperature is measured with an infrared thermometer. Data analysis was done by plotting the relationship between a thick layer of sponge on the temperature inside the miniature house. Results obtained indicating that the air temperature in the house miniature dropped significantly 2 oC-8 oC lower than the outside air temperature. Keywords: roof, aluminum, temperature.